Odpowiedzi

2009-11-03T15:54:35+01:00
3,4a+0,4b-7,2c=3,4*1+0,4*(-1)-7,2*(-1)=3,4-0,4+7,2=10,2

3,4a+0,4b-7,2c=3,4*1/4+0,4*3/4-7,2*1/6=34/10*1/4+4/10*3/4-72/10*1/6=34/40+3/10-12/10=34/40+12/40-48/40=-2/40=-1/20

3,4a+0,4b-7,2c=3,4*(-10,4*1-7,2*1=-3,4+0,4-7,2=-10,2
2009-11-03T15:56:48+01:00
3,4x¼+0,4x¾-7,2x⅙ =
³⁴/₁₀ x ¼ + ⁴/₁₀ x ¾ - ⁷²/₁₀ x ⅙ = ³⁴/₄₀ + ³/₁₀ - ¹²/₁₀=
³⁴/₄₀ + ¹²/₄₀ - ⁴⁸/₄₀ = ⁹⁴/₄₀ = 2 ¹⁴/₄₀ = 2 ⁷/₂₀


3,4 x(-1) +0,4 x 1 - 7,2 x 1= -3,4 + 0,4 - 7,2 = 11
Najlepsza Odpowiedź!
2009-11-03T16:54:54+01:00
Dla a=1, b=-1, c=-1
3,4a+0,4b-7,2c=3,4•1+0,4•(-1)-7,2•(-1)=3,4-0,4+7,2=10,2

dla a=¼, b=¾, c=⅙
3,4a+0,4b-7,2c=3,4•¼+0,4•¾-7,2•⅙=34/10•¼+4/10•¾-72/10•⅙=17/5•¼+2/5•¾-36/5•⅙=17/20+6/20-36/30=23/20-36/30=69/60-72/60=-3/60=-1/20=-0,05

dla a=-1, b=1, c=1
3,4a+0,4b-7,2c=3,4•(-1)+0,4•1-7,2•1=-3,4+0,4-7,2=-10,2